Popular Couple clebrates 55th (Raton Range Raton, New Mexico, 1989)
Newspaper Article on the 55th Anniversary of Muriel and Oscar Gregory.
Master list item #: 24
File location is in the Raton File Cabinet
Keywords: Gregory, Oscar; Gregory, Muriel; Kepner, John; Gregory, Richard; Gregory, Beverly; Warmuth, Bob; Warmuth, Beth; Gregory, James; Gregory-Rudd, Julie; Warmuth, Greg; Warmuth, Mark; Warmuth, Lynne; First United Methodist Church; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Chicago, Illinois; Ft. Collins, Colorado; Hickey, North Carolina